Improved Vertical Streambed Flux Estimation Using Multiple Diurnal Temperature Methods in Series. Issue 1 (22nd June 2016) - Irvine, D. J.; Briggs, M. A.; Cartwright, I.; Scruggs, C. R.; Lautz, L. K.
Abstract: Analytical solutions that use diurnal temperature signals to estimate vertical fluxes between groundwater and surface water based on either amplitude ratios ( Ar ) or phase shifts (Δ ϕ ) produce results that rarely agree. Analytical solutions that simultaneously utilize Ar and Δ ϕ within a single solution have more recently been derived, decreasing uncertainty in flux estimates in some applications. Benefits of combined ( Ar Δ ϕ ) methods also include that thermal diffusivity and sensor spacing can be calculated. However, poor identification of either Ar or Δ ϕ from raw temperature signals can lead to erratic parameter estimates from Ar Δ ϕ methods. An add‐on program for VFLUX 2 is presented to address this issue. Using thermal diffusivity selected from an Ar Δ ϕ method during a reliable time period, fluxes are recalculated using an Ar method. This approach maximizes the benefits of the Ar and Ar Δ ϕ methods. Additionally, sensor spacing calculations can be used to identify periods with unreliable flux estimates, or to assess streambed scour. Using synthetic and field examples, the use of these solutions in series was particularly useful for gaining conditions where fluxes exceeded 1 m/d.